COVID-19-related stressful experiences and posttraumatic stress disorder symptoms among college students in China: A moderated mediation model of perceived control over the future and empathy. (August 2022) - Ye, Zhi; Zeng, Chengbo; Yang, Xueying; Tam, Cheuk Chi; Wang, Yuyan; Qiao, Shan; Li, Xiaoming; Lin, Danhua
The current study aims to investigate the mediating effect of perceived control over the future and the moderating effect of empathy on the association between stressful experiences and PTSD symptoms among college students in China in response to COVID-19. A sample of 1, 225 college students (70.69% were female, M age = 20.22 years, SD  = 2.02) were recruited using web-based surveys at wave 1 (W1) and wave 2 (W2) longitudinally. Results showed that COVID-19-related stressful experiences were significantly associated with PTSD symptoms. Perceived control over the future partially mediated the relationship between these two variables ( indirect effect size  = 0.09, p < 0.01). Empathy significantly moderated the path from perceived control over the future to PTSD symptoms, suggesting that the association was stronger for individuals with higher levels of empathy. Findings suggest a protective effect of perceived control over the future on college students' PTSD symptoms during the COVID-19 pandemic. Such a protective effect was intensified by empathy. Future intervention to manage PTSD symptoms should be tailored to positive future expectations and empathy.